The Moderating Role of Firm Size: Pengaruh Capital Structure, Current Ratio dan Profitability Terhadap Company Value - Keisya Novadila Putri; Imronudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines company value with firm size moderation in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sample consists of 38 companies per year, selected using the purposive sampling method, resulting in a total of 152 data points over four years. The research variables include Debt to Asset Ratio (DAR), Current Ratio (CR), Return on Assets (ROA), firm size (log of total assets), and company value (Tobin's Q). Multiple linear regression analysis is employed to assess the impact of independent variables on company value, while Moderated Regression Analysis (MRA) is used to evaluate the moderating role of firm size. The findings indicate that capital structure, current ratio, and profitability positively and significantly affect company value. Firm size is shown to moderate the relationship between capital structure and current ratio with company value but does not moderate the relationship between profitability and company value. The study recommends expanding the data and research period and exploring other moderating variables to provide deeper insights into the factors influencing company value.